Rancang Bangun Sistem Rekomendasi Destinasi Wisata Di Bondowoso Berbasis Website - Dinda Riski Priska Wati; A. Hamdani (Jurnal Mahasiswa Teknik Informatika, 2025)
Bondowoso Regency has highly attractive natural, cultural, and historical tourism potential, yet tourists face difficulties in determining destinations that match their preferences, time, and budget due to the lack of structured information. This research aims to design and develop a website-based tourism destination recommendation system to assist tourists in selecting tourism destinations in Bondowoso personally and efficiently. Data collection methods were conducted through interviews with DISPARBUDPORA of Bondowoso Regency, documentation study, and literature study. System development uses the System Development Life Cycle (SDLC) method with a waterfall model covering analysis, design, implementation, testing, and maintenance stages. The system is designed with automatic recommendation features based on tourism type, travel distance, facilities, and budget. The research results in a web-based system that provides complete information on tourist attractions, personal recommendation features, and an admin dashboard for data management. This system is expected to help tourists save travel planning time, increase tourist visit satisfaction, and support the promotion of Bondowoso regional tourism more effectively and efficiently. Keywords: Recommendation System, Tourism Destination, Bondowoso, Website, SDLC Waterfall  Kabupaten Bondowoso memiliki potensi wisata alam, budaya, dan sejarah yang sangat menarik, namun wisatawan mengalami kesulitan dalam menentukan destinasi yang sesuai dengan preferensi, waktu, dan budget mereka akibat keterbatasan informasi yang terstruktur. Penelitian ini bertujuan merancang dan membangun sistem rekomendasi destinasi wisata berbasis website untuk membantu wisatawan dalam memilih destinasi wisata di Bondowoso secara personal dan efisien. Metode pengumpulan data dilakukan melalui wawancara dengan DISPARBUDPORA Kabupaten Bondowoso, studi dokumentasi, dan studi pustaka. Pengembangan sistem menggunakan metode System Development Life Cycle (SDLC) dengan model waterfall yang meliputi tahap analysis, design, implementation, testing, dan maintenance. Sistem dirancang dengan fitur rekomendasi otomatis berdasarkan jenis wisata, jarak tempuh, fasilitas, dan budget. Hasil penelitian berupa sistem berbasis web yang menyediakan informasi lengkap objek wisata, fitur rekomendasi personal, dan dashboard admin untuk pengelolaan data. Sistem ini diharapkan dapat membantu wisatawan menghemat waktu perencanaan perjalanan, meningkatkan kepuasan kunjungan wisata, serta mendukung promosi pariwisata daerah Bondowoso secara lebih efektif dan efisien. Kata Kunci: Sistem Rekomendasi, Destinasi Wisata, Bondowoso, Website, SDLC Waterfall